Negotiating Solidarity - Mohamed Fouz Mohamed Zacky (PCD Journal, 2025)
In a recent study, Huberman (2025) argues that Latin American leftist governments, despite expressing solidarity with the Palestinian cause, are constrained by the global order and the capitalist system in further deepening its strategic influence on the Israel-Palestine conflict. Drawing on this insight, the present study examines how Sri Lanka’s newly elected National People’s Power (NPP)-led government has responded to the ongoing Israeli occupation and genocide in Gaza. Similar to cases in Latin America, the Sri Lankan context is particularly pertinent given the NPP’s left-leaning orientation. This study argues that, despite the party’s anti-imperialist ideological commitment to the Palestinian cause, the NPP largely replicates the trajectory of previous administrations—reaffirming support for Palestinian self-determination while simultaneously pursuing strategic engagement with Israel. Crucially, the government has refrained from adopting substantive measures to alter this established pattern, even amid global condemnation of Israel’s disproportionate bombardment of Gaza. A key factor constraining its response is Sri Lanka’s economic vulnerability. Finally, beyond supporting international resolutions, the study recommends that the government clearly articulate its opposition to Israel’s ongoing military assault in Gaza and implement concrete measures—such as ensuring that tourism, trade, and other exchanges even do not indirectly support the Israeli illegal occupation of Palestine.